L’écriture créative : technique efficace pour favoriser l’expression écrite en classe de FLE - Luchkevych, Viktoriia (2022)
The paper aims to show the importance of creativity in the class of French as a Foreign Language (FLE). Thobjectives defined in this study are the deepening of theoretical knowledge as well as the search for teachingtechniques to work on the writing skills in the course of FLE in a creative and effective way. Creative writing hasbeen analyzed as an effective technique of teaching a foreign language, contributing to the activation of the students’cognitive activity and increasing their interest in language learning. The paper shows didactic strategies that focus oncreative writing activities as a motivating factor for learners.
Keywords: creative writing; FLE; motivation; creativity; written expression